Perfectionism and sport-specific engagement in elite youth soccer players - Larkin, P.; O`Connor, D. Williams, A. M. (Journal of Sports Sciences, 2016)
It is acknowledged that the time invested in sport-specific activities contributes to higher levels of performance. However, there is limited understanding of the potential impact of personality traits, such as perfectionism, on engagement in sport-specific activities. In the current study, we examine whether elite youth soccer players who demonstrate higher and lower levels of perfectionistic strivings tendencies can be differentiated based on their sport-specific engagement. The Sport Multidimensional Perfectionism Scale 2 and an adapted Player History Questionnaire were completed by 419 elite youth male soccer players competing at the Australian age-related national youth championships (under 13, n = 133; under 14, n = 166; under 15, n = 120). A quartile split approach was used to separate higher (n = 100) and lower (n = 107) perfectionistic strivings groups. Findings revealed the higher perfectionistic strivings group accumulated more time in sport-specific activities, including coach-led practice, individual practice, peer-led play and indirect involvement in soccer when compared to individuals with lower perfectionistic strivings tendencies. Descriptive analysis indicates this equates to approximately 159 h a year (i.e. 17 h coach-led practice, 22 h individual practice, 60 h of peer-led play and 60 h of indirect involvement) more than the lower perfectionistic strivings group. In summary, the results suggest players with varying levels of perfectionistic strivings may be differentiated based on their engagement in soccer-specific activity in a sample of elite youth players in Australia, and suggests that perfectionistic strivings may have an adaptive influence on sport-specific engagement.